Implementation of the Authority of the Indonesian Ombudsman Representative of the Province of Nusa West Southeast in Oversight of Public Services in the Village - Rachman Maulana Kafrawi; Khairul Umam; Muh. Alfian Fallahiyan (Fakultas Hukum Universitas Mataram, 2023)
The Ombudsman is an institution established to deal with abuse of power by government officials and to assist officials in carrying out government efficiently and fairly, as well as to encourage power holders to carry out their responsibilities and provide good service. The Ombudsman Representative for West Nusa Tenggara Province has a role in supervising public services in their working area. In following up on each report complained by the complainant, the Ombudsman will ensure whether the report falls under the authority of the Ombudsman or not. This study aims to see the effectiveness of the Ombudsman in supervising public services in the village. The research method is socio-legal. Socio-legal research represents an interface with a context whitin which law exists. In supervising public services, apart from receiving reports from the public, the Ombudsman can also carry out on his own initiative through a systemic review, the results of which can be in the form of recommendations/suggestions. To ensure compliance with efforts to resolve the Ombudsman by the Reported Party or the Reported Party's superiors, the Ombudsman conducts direct monitoring or through the media/publications and submits periodic and annual reports to the President of the Republic of Indonesia and the People's Representative Council.